2007
DOI: 10.1016/j.clinph.2007.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Updating P300: An integrative theory of P3a and P3b

Abstract: The empirical and theoretical development of the P300 event-related brain potential (ERP) is reviewed by considering factors that contribute to its amplitude, latency, and general characteristics. The neuropsychological origins of the P3a and P3b subcomponents are detailed, and how target/ standard discrimination difficulty modulates scalp topography is discussed. The neural loci of P3a and P3b generation are outlined, and a cognitive model is proffered: P3a originates from stimulusdriven frontal attention mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

458
6,265
38
74

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6,334 publications
(7,079 citation statements)
references
References 304 publications
458
6,265
38
74
Order By: Relevance
“…The hypothesis that the LC-NE system contributes to P3 generation during a target detection task is consistent with the allocation of attentional resources and arousal effects in humans [13,[17][18][19]. Monkey studies with the oddball paradigm have shown that the conditions for generating the P3 are highly similar to those for the LC phasic response: both are preferentially elicited by attended, task-relevant, arousing, and salient stimuli that are important for goal-directed behavior [15,20].…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…The hypothesis that the LC-NE system contributes to P3 generation during a target detection task is consistent with the allocation of attentional resources and arousal effects in humans [13,[17][18][19]. Monkey studies with the oddball paradigm have shown that the conditions for generating the P3 are highly similar to those for the LC phasic response: both are preferentially elicited by attended, task-relevant, arousing, and salient stimuli that are important for goal-directed behavior [15,20].…”
Section: Introductionsupporting
confidence: 54%
“…Monkey studies with the oddball paradigm have shown that the conditions for generating the P3 are highly similar to those for the LC phasic response: both are preferentially elicited by attended, task-relevant, arousing, and salient stimuli that are important for goal-directed behavior [15,20]. Furthermore, the timing and topographic distribution of intracranial and scalp-recorded P3 activity are consistent with the anatomical and physiological activation of temporoparietal areas by the LC-NE system [13,15]. Finally, lesions of the LC cell bodies reduce the auditory P3 amplitude in monkeys, indicating that the LC nucleus and its ascending fibers are important in the generation and modulation of the P3 [21].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations